SUSŢINEREA INFORMAŢIONALĂ ŞI DOCUMENTARĂ A CERCETĂRILOR ŞTIINŢIFICE UNIVERSITARE - TOPALO, Valentina (BIBLIOPOLIS, 2020)
The Scientific Library of the State University „A. Russo”, Balti participates to the research and study process, offering information services, necessary to the: acquisition, conservation, collection management. The library is involved in 16 research projects, 12 institution projects, 1 state project, and 3 university projects. All researches are supported by the logistic and efforts of its employees. In 2007 was founded the Council of Science Research in order to elaborate the strategies and research directions. The library collaborates with Journal Donation Project, World Bank, Council of Europe, NATO, and UNDP. The users have access to the Internet and international databases: EBSCO, GREEN FILE, AGORA, HEIN on-line, databases of ONU, Council of Europe, NATO, World Bank, Jurist, local OPAC, Scanned Summary, collection, online exhibitions.